The Relationship between Fear of Childbirth and Women’s Knowledge about Painless Childbirth - Mehmet Aksoy; Ayse Nur Aksoy; Aysenur Dostbil; Mine Gursac Celik; Ilker Ince (Obstetrics and Gynecology International)
This study investigated the association between fear of childbirth (FOC) and women’s knowledge about painless childbirth methods. The study was performed on 900 multiparous women within the last month of pregnancy. Data was obtained through a questionnaire including the Wijma Delivery Expectancy/Experience Questionnaire (W-DEQ) Turkish form A. FOC was defined as W-DEQ sum score ≥85. Women were questioned about their knowledge about painless childbirth and the most important source of this knowledge. Group 1 consists of participants with knowledge about painless childbirth. Group 2 consists of participants without knowledge about painless childbirth. Five hundred and twenty-four women (58.2%) had knowledge while 376 women (41.7%) had no knowledge about painless childbirth. Mean W-DEQ scores in group 1 (68.46±12.53) were found to be lower than group 2 (71.35±12.28) (P=0.001). FOC was associated with increased maternal request for elective caesarean section (OR 4.22, 95% CI 2.91–6.11). Better informed pregnant women about painless childbirth methods may reduce the number of women with FOC and the rate of preferred elective caesarean section.